Buyer power and mutual dependency in a model of negotiations. - Inderst, Roman; Montez, Joao (RAND Journal of Economics (Wiley-Blackwell))
We study bilateral bargaining between several buyers and sellers in a framework that allows both sides, in case of a bilateral disagreement, flexibility to adjust trade with each of their other trading partners and receive the gross benefit generated by each adjustment. A larger buyer pays a higher per‐unit price when buyers' bargaining power in bilateral negotiations is sufficiently low, and a lower price otherwise. An analogous result holds for sellers. These predictions, and the implications of different technologies, are explained by the fact that size is a source of mutual dependency and not an unequivocal source of power.